INDEPENDENT LEARNING STRATEGY OF NATURAL SCIENCE WITH âONE DAY ONE DIARY FOR SCIENCEâ PROGRAM - Herlianti, P. S.; Linuwih, S.; Dwijananti, P. (Physics Department, Faculty of Mathematics and Natural Sciences, Semarang State University, 2015)
Learning behavior and metacognitive skill of students affect cognitive value and level of understanding of each student. The application of the